Efficacy of Transcatheter Arterial Embolization for Hemorrhage Control in Traumatic Hepatic Injury With Celiac Axis Stenosis - Yook Kim; Younghoon Sul (Emergency Medicine International)
Conclusion: TAE is a safe and effective intervention for managing hemorrhage in traumatic liver injury complicated by CAS. Thorough assessment of computed tomography images is crucial for diagnosing the underlying causes of CAS and optimizing catheterization strategies.